The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2019
DOI: 10.36510/learnland.v12i1.989
|View full text |Cite
|
Sign up to set email alerts
|

Creating a Context for Girl of Color Ways of Knowing Through Feminist of Color Playwriting

Abstract: This article investigates how playwriting served three middle school Black girls within a larger practitioner research study seeking to better understand the literate practices of girls of color. It delves into the ways that playwriting provided the girls in an afterschool writing club opportunities to explore both their knowledge and ways of knowing, rooted in their cultural, gendered, and racialized experiences, and, in turn, share these with others, within an academic setting. It points to the necessity for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…First, our findings underscore the primacy that digital technology holds over organizing sanctioned literacy practices, as well as how care and empathetic human intra-actions can decenter the role machines play within assemblages. Player (2019, p. 224), argues that literacy scholarship that centers on minoritized girls enables literacy scholars to understand the ways that oppressive practices harm girls of color, “as well as the ways that they are brilliant, agentive and passionate.” We illuminate the agency the girls exercised in finding alternate ways to participate that bolstered their subjectivities against institutional erasure. For example, in repositioning their bodies in relation to one another and the recording devices, Rhianna, Isa and Jillian agentically disrupted and subverted institutionalized discourses that position Black girls as less nurturing, less in need of protection, support and comfort than their white counterparts (Epstein et al , 2017; Richardson, 2009; Wun, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…First, our findings underscore the primacy that digital technology holds over organizing sanctioned literacy practices, as well as how care and empathetic human intra-actions can decenter the role machines play within assemblages. Player (2019, p. 224), argues that literacy scholarship that centers on minoritized girls enables literacy scholars to understand the ways that oppressive practices harm girls of color, “as well as the ways that they are brilliant, agentive and passionate.” We illuminate the agency the girls exercised in finding alternate ways to participate that bolstered their subjectivities against institutional erasure. For example, in repositioning their bodies in relation to one another and the recording devices, Rhianna, Isa and Jillian agentically disrupted and subverted institutionalized discourses that position Black girls as less nurturing, less in need of protection, support and comfort than their white counterparts (Epstein et al , 2017; Richardson, 2009; Wun, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Ngo found that girls tended to place extra focus on the tensions around gender expectations between Hmong culture and U.S. values. In my own work in an after-school GOC writing program (Player, 2018(Player, , 2019(Player, , 2021, I found that GOC, including AsAm girls, used genre, such as playwriting and poetry, while tapping into raced, gendered epistemological resources to understand themselves as complex individuals with hybrid identities often ignored by dominant discourses. In work with AsAm girls in an intergenerational inquiry group, Ghiso, Campano, Player, Krishanwongso, and Gultom (2020) found that the girls used coalitional literate practices toward refusing assimilation and, in turn, committing to a shared commitment to educational equity.…”
Section: Asam Girl Literaciesmentioning
confidence: 99%
“…3 Although beyond the scope of this article, in regard to solidarity, there were shared sentiments about the importance of relationships across difference, and commitment to understandings of concepts such as feminism were codeveloped by many of the Sisters across various identities. This work has been more fully explored in other articles about the Unnormal Sisterhood (Player, 2019(Player, , 2021.…”
Section: Notesmentioning
confidence: 99%
“…This work sits in the company of scholars who have explored the ways Black girls resist and survive oppressive systems, including schooling, while also highlighting Black joy, creation, and ingenuity (Brown, 2009; 2013; Kelly, 2020; Richardson, 2007; Winn, 2011). The scholarship on Black girl literacies emphasizes the power of critical, humanizing, and multimodal pedagogies and how they can support educators in honoring the knowledge of Black girls (Player, 2019, 2021; Price-Dennis, 2016; Muhammad & Womack, 2015; Turner & Griffin, 2020). Further, this important work documents how Black girls are multifaceted, multidimensional, and have a variety of unique and intersecting identities that impact their lived realities and, thus, their literacies (Ife, 2017; Muhammad, 2015; Smith, 2016).…”
Section: Framing Girl Of Color Literaciesmentioning
confidence: 99%